Role of PARP Inhibitors in Glioblastoma and Perceiving Challenges as Well as Strategies for Successful Clinical Development - Bisht, Priya; Kumar, V. Udaya; Pandey, Ruchi; Velayutham, Ravichandiran; Kumar, Nitesh (Frontiers in Pharmacology, 2022)
Glioblastoma multiform (GBM) is the most aggressive primary type brain tumor, representing 54% among all gliomas. The average life span for glioblastoma multiform is around 14 to 15 months instead of treatment. The current treatment for glioblastoma multiform includes surgical removal of the tumor followed by radiation therapy and temozolomide chemotherapy for 6.5 months, followed by another 6-month of maintenance therapy with temozolomide chemotherapy (5 days every month). However, resistance to temozolomide is frequently one of the limiting factors in the effective treatment. Poly (ADP-Ribose) polymerase (PARP) inhibitors have recently been investigated as sensitizing drugs to enhance temozolomide potency. However, clinical use of PARP inhibitors in glioblastoma multiform is difficult due to a number of factors such as limited blood-brain barrier penetration of PARP inhibitors, inducing resistance due to frequent use of PARP inhibitors, overlapping hematologic toxicities of PARP inhibitors when co-administered with glioblastoma multiform standard treatment (radiation therapy and temozolomide). This review elucidates the role of PARP inhibitors in temozolomide resistance, multiple factors that make development of these PARP inhibitor drugs challenging and the strategies such as development of targeted drug therapies, combination therapy to combat the resistance of PARP inhibitors can be adopted to overcome these challenges.